2011
DOI: 10.4103/0973-1075.78445
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of palliative care among diploma nursing students

Abstract: Background:The goal of palliative care is not to cure, but to provide comfort and maintain the highest possible quality of life for as long as life remains. The knowledge of nurses influences the quality of care provided to these patients. The present study aimed at identifying the level of knowledge and attitude of nursing students who are the future caretakers of patients, which helps to make recommendations in incorporating palliative care concepts in the nursing curriculum.Objectives:(1) To assess the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
3
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 1 publication
6
40
3
5
Order By: Relevance
“…Similarly, Canning et al (2004) highlighted the importance of palliative care education for nurses, noting that more than half of a sample of nurses reported feeling unprepared for palliative care, with 63% disclosing a lack of opportunity for further study, and 44% reporting a lack of inservice training. Also, Karkada et al (2011) investigated palliative care knowledge among nursing students. Only 43.4% of them were aware of the term palliative care and it was during their training period.…”
Section: Theoretical Considerations and A Selected Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Canning et al (2004) highlighted the importance of palliative care education for nurses, noting that more than half of a sample of nurses reported feeling unprepared for palliative care, with 63% disclosing a lack of opportunity for further study, and 44% reporting a lack of inservice training. Also, Karkada et al (2011) investigated palliative care knowledge among nursing students. Only 43.4% of them were aware of the term palliative care and it was during their training period.…”
Section: Theoretical Considerations and A Selected Literature Reviewmentioning
confidence: 99%
“…A significant amount of literature has been devoted to assess the knowledge and attitudes of healthcare professionals towards palliative care and have highlighted inadequacies in nurses' skills and knowledge in palliative care (Karkada et al, 2011;Rolandson et al, 2008;Bickel-Swenson, 2007;Canning et al, 2004;Becker, 2000;Farrell, 1998;McCaffery & Ferrell, 1997;Morgan, 1997). An important tool for assessing knowledge and attitudes towards palliative care is the Palliative Care Quiz for Nursing (PCQN).…”
Section: Theoretical Considerations and A Selected Literature Reviewmentioning
confidence: 99%
“…Abudari et al (2014) (47) and Dunn et al (2005) (40) revealed that most participants demonstrated a positive attitude about providing care for dying patients. Furthermore, Kassa et al (2014) (2) and , Karkada et al (2011) (48) demonstrated that (76% and 92.8% respectively) of the studied nurses had favorable attitude towards PC.…”
Section: Discussionmentioning
confidence: 99%
“…Role of physiotherapists and nurses is as important as palliative care physician for better outcome of palliative care. [7][8][9][10] Palliative medicine has become a medical specialty in UK and other European Countries in 1987 but it is still underdeveloped in a developing country like India.…”
Section: Discussionmentioning
confidence: 99%